Respuesta :

Answer:

3 ± i sqrt( 7)

-------------------------------

      4

Step-by-step explanation:

2x^2+2=3x

Subtract 3x from each side

2x^2 -3x+2=0

Using the quadratic formula

-b ± sqrt( b^2 -4ac)

-------------------------------

      2a

a =2  b = -3   c =2

-(-3) ± sqrt( (-3)^2 -4*2*2)

-------------------------------

      2*2

3 ± sqrt( 9 - 16)

-------------------------------

      4

3 ± sqrt( -7)

-------------------------------

      4

sqrt(-7) = sqrt(-1) sqrt(7) = i sqrt(7)

3 ± i sqrt( 7)

-------------------------------

      4

ACCESS MORE